Retrospective study of correction of rigid adult clubfoot or equinovarus deformity using Ilizarov technique, outcomes in Pakistan - Dina, Twahir Kalekhan; Rahim, Muhammad Kazim; Peracha, Muhammad Asif; Aziz, Sobia; Shah, Sayed Moinuddin; Noor, Syed Shahid (Journal of the Pakistan Medical Association, 2026)
Abstract Objectives: To assess the outcomes of correction of adult equinovarus clubfoot with Ilizarov technique. Method: The retrospective study was conducted from December 2023 to January 2025 at the Department of Orthopaedic Surgery, Liaquat National Hospital and Medical College, Karachi, and comprised data from 2015 to 2025 of adults with rigid equinovarus deformity who were treated with the Ilizarov construct of 2 tibial full-rings, one half-ring for forefoot and hindfoot, and tendo-Achilles lengthening for gradual correction. Outcomes were assessed using American Orthopaedic Foot and Ankle Society score and Reinker-Carpenter scale, preoperatively and 12 months post-surgery. Data was analysed using SPSS 22. Results: Of the 38 patients with mean age 23.7±6.2 years, 26(68.4%) were male and 12(31.6%) were female. There were 29(76.3%) unilateral and 9(23.7%) bilateral cases. There were 10(21.3%) cases of congenital neglected clubfoot, 22(46.8%) cases of recurrent/resistant clubfoot, 4(8.5%) cases of neuromuscular/spinal pathology, 3(6.4%) cases of post-polio deformity, 7(14.9%) cases of posttraumatic deformity, and 1(2.1%) case of hemimelia. Mean frame duration was 16.3±5.1 weeks, and follow-up time was 28.5±12.2 months. At frame removal, Reinker-Carpenter score was excellent in 6(12.8%) cases, good in 30(63.7%), fair in 8(17%), and poor in 3(6.5%). There was 1(2.1%) case of supination deformities and 5(%) of claw foot requiring adjunct surgery, and 1(2.1%) case of acute posterior-tibial-nerve palsy with treatment abandonment. Mean American Orthopaedic Foot and Ankle Society score increased from 29.6±19.2 to 81.4±12.3 postoperatively. Conclusion: Ilizarov fixator with tendo-Achilles lengthening allowed controlled correction of rigid clubfoot deformity with minimal complications. Ankle-foot-orthosis could minimise any residual deformitiy. Ankle stiffness was commonplace. Key Words: Ilizarov, Rigid clubfoot, Equinovarus deformity.